The Development of The Labour Law of the European Union in 2019 – New Sources and New Perspectives for a More Reliable Legal Framework of Labour Relations. Part One: European Labour Authority – Establishment and Legal Characteristic - Staykov, Ivaylo (Yearbook of the Law Department, 2020)
In 2019 the development of the labour law of the EU received a strong impetus. The questions of the EU social policy were among the leading activities of all EU institutions. Two acts in the field of EU social policy, adopted in 2019, attract attention because they are expected to have a structural role in the future development of European labour and social law. These are Regulation (EU) 2019/1149 and Directive (EU) 2019/1152. Both acts were adopted under the ordinary legislative procedure, both acts have an identical story about their adoption, and were not accidentally adopted on the same date and published in the same issue of the OJ of the EU. The adopted acts of the EU law in the social field are the logical final step in the multi-year progressive efforts for adequate coping with the many problems and challenges facing the internal market, incl. labour market, which became a reality in the second decade of the 21st century. Given the size of the normative content of both acts, their social and legal purpose and importance of labour law and social policy of the EU, it is necessary to analyse them separately. In the following lines, as part one of a more comprehensive study, will be presented the background and establishment of the European Labour Authority, as well as its legal characteristic – functions and bodies. The statement does not claim to be exhaustive – it marks the beginning of a study on the place and role of this new body in the ever-current EU social policy.